Unmasking the Resistance: Detecting Carbapenem Genes in Acinetobacter baumannii Isolated from some Hospitals in Najaf and Baghdad - Jasim, Muhammad Kareem; Hadi, Zainab Jaber; Alsherees, Hashim Ali Abdualmeer; Annooz, Aaedah (Medical Science Journal for Advance Research, 2023)
Acinetobacter baumannii is a multidrug-resistant bacterium associated with nosocomial infections and known for its ability to develop resistance rapidly. Carbapenem-resistant A. baumannii (CRAB) is a top priority pathogen according to the World Health Organization (WHO). We focused on evaluating the susceptibility of A. baumannii to antibiotics, detecting carbapenemase enzymes using the modified Hodge test, and characterizing the presence of specific carbapenem resistance genes using PCR analysis.This cross-sectional study took place at Al-Sader Medical City and Baghdad Teaching Hospitals from October 2022 to February 2023. It involved 59 A. baumannii isolates collected from patients. The isolates were obtained and processed for accurate diagnosis using morphological techniques, biochemical tests, and Vitek2 systems. The Kirby-Bauer method was employed to assess the susceptibility of the isolates to 24 antibiotics. DNA extraction and PCR analysis were conducted to detect carbapenem resistance genes, 59 specimens from patients, including sputum, wound swabs, blood, and inguinal swabs were analyzed. The majority of isolates were from in-patients, showing a significant difference compared to outpatients. Our finding revealed that among the studied isolates, blaSPM was the most prevalent gene, detected in 50% of the isolates. This indicates a significant presence of blaSPM-mediated carbapenem resistance among A. baumannii strains in our study population.Furthermore, our findings demonstrated alarmingly high resistance rates against the majority of antibiotics commonly prescribed to treat A. baumannii infections. A striking 95% of the isolates were classified as extensively drug-resistant, indicating resistance to multiple classes of antibiotics. This poses significant challenges for effective treatment options and underscores the urgent need for alternative strategies in managing A. baumannii infections.